Georgia : First Review under the Extended Fund Facility and Request for Modification of Performance Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Georgia's First Review Under the Extended Fund Facility (EFF) and Request for Modification of Performance Criteria (PCs). The program is on track with all end-June 2017 performance criteria and structural benchmarks met. Economic activity has strengthened on the back of stronger growth in main trading partners. Fiscal overperformance and efforts to address structural weaknesses have helped boost confidence. The economic recovery is gaining momentum, inflation is projected to decline starting in early 2018, and the external position has strengthened. The IMF staff supports the authorities' request for completion of the First Review under the EFF and the modification of three quantitative PCs.